Penerapan Model Pembelajaran Project Based Learning Berbasis Lesson Study Melalui Pembelajaran Daring Untuk Mengetahui Kemampuan Berfikir Kritis Dan Hasil Belajar - I Gusti Ayu Agung Sinta Diarini; Maria Fransisca Br Ginting; I Wayan Suryanto (Jayapangus Press, 2020)
Project-based learning in learning activities carried out online or learning from home, is expected to be a learning model, packaged attractively, emphasizing the development of critical thinking skills to solve the problems being faced, and able to improve student learning outcomes. This type of research is classroom action based research study with two cycles, the method of collecting data with tests, questionnaires, interviews and observations, analyzed with quantitative descriptive methods. The results showed the average critical thinking ability in the first cycle was 72.5% with a good category, increasing in the second cycle to 88.3% with a very good category. The average learning outcomes of the first cycle was 79.7% with good categories and the second cycle was 80.8% with good categories. The application of the Project Based Learning model based on lesson study through online learning, is able to improve the critical thinking skills of students with excellent categories, and the learning outcomes of class XI TB 1 students at SMK PGRI 1 Badung with good categories.